Study of Oil Palm (Elaeis guineensis Jacq) In Vitro Embryogenesis using Young Leaves Explants - Wiendi, Ni Made Armini; Constantin, Mondjeli; Wachyar, Ade (Journal of Tropical Crop Science, 2015)
This study reported in vitro embryogenesis of oil palm using young leaves as explants. Explants were grown in solid modified MS or Eeuwens medium containing different concentrations of NAA and 2,4-D, i.e. media C1, C2, C3, C4 and C5, M1, M2, M3 and M4, to induce embryogenic calli. Compact and pearly-white, globular calli were obtained from the youngest leaf explants 28 weeks after culture.C1 media (MS medium + 107.41 µM of NAA + 100 mg.L-1 of asparagine + 100 mg.L of glutamine-1) produced the highest percentage of calli formation (30.56%), whereas C4 media (C1 supplemented with 67.86 µM of 2,-D ) was the optimal media for embryogenic callus induction. Direct embryoids were obtained from slightly older leaf explants on the C3 media containing NAA after 36 weeks of culture. However, four subcultures using the same medium with gradual reduction of auxin concentration were not successful to develop embryogenic callus and embryoid cells during the course of this study.